ENGLISH FOR INFORMATICS ENGINEERING: NEEDS ANALYSIS - Septian Nasution, Sukma; Nur Najibah Sukmawati, Lodya Sesriyani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
English for Vocational School is a key to bridging non-English major students’ needs including Informatics Engineering students of a private university in South Tangerang, Indonesia. Accordingly, it is important to conduct a needs-analysis study as a way to find the source of information to designing proper English materials. To actualize it, a set of questionnaire was distributed to 35 students of Informatics Engineering Study Program to investigate their necessities, lacks, and desire in learning English for vocational purpose. The data were analysed quantitatively to figure out majority choices to each item questioned. Semi-structured interview to both the lecturers and the students were also conducted to explore reasons for each finding. The result showed that the students were expected to be proficient at using English for daily communication which will be useful for their future working-community because most of the students thought that they were not fluent yet and found difficulties especially in grammar mastery. Accordingly, they expected that instructional process be directed to learning English related to Informatics Engineering without ignoring daily communication topics. These overall findings are a milestone to designing a set of English learning materials for the third semester students of Informatics Engineering Students of the university.